2003
DOI: 10.1029/2002gl015775
|View full text |Cite
|
Sign up to set email alerts
|

Convergent flow observed in a laboratory‐scale unsaturated fracture system1

Abstract: [1] An experiment was designed to observe water flow in a simple analogue fractured rock network. The fracture network was modeled by the gaps between an array of limestone blocks, whose permutations generated different realizations of the network. Three out of five of these realizations displayed flow convergence, in contrast to that predicted by porous continuum models. Such convergence occurs because fracture intersections act as capillary barriers that integrate or focus flow within the network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 10 publications
5
26
0
Order By: Relevance
“…Recent results from both laboratory and field experiments in fractured rock suggest that fracture intersections can force the convergence of pathway; flow from an intersection need not be divided amongst all exiting fractures but can be directed into only one [ Glass et al , 2002b; LaViolette et al , 2003]. Laboratory experiments have also shown that fracture intersections can act as hysteretic gates that integrate flow from above until a threshold volume is exceeded, and then release all or a portion of the volume as a pulse below [ Glass et al , 2002a; Wood et al , 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results from both laboratory and field experiments in fractured rock suggest that fracture intersections can force the convergence of pathway; flow from an intersection need not be divided amongst all exiting fractures but can be directed into only one [ Glass et al , 2002b; LaViolette et al , 2003]. Laboratory experiments have also shown that fracture intersections can act as hysteretic gates that integrate flow from above until a threshold volume is exceeded, and then release all or a portion of the volume as a pulse below [ Glass et al , 2002a; Wood et al , 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Unsaturated flow experiments in fracture networks indicate that intersections can direct flow to a single exiting fracture [ LaViolette et al , 2003]. In addition, they have been found to gather water from above to release as a pulse below [ Wood et al , 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Projection of our results to a regular network of equal aperture vertical and horizontal fractures suggests substantial differences between wetting and nonwetting flows. The absence of entry into the horizontal fractures by the nonwetting phase would preclude the following phenomena observed for wetting phase flow: macroscopic flow convergence [ LaViolette et al , 2003], pathway switching [ Glass et al , 2002, 2003], and temporal fluctuations in outflow over a range of scales [ Glass et al , 2002]. Instead, we expect that the nonwetting phase would move rapidly along narrow pathways through the vertical fractures, establishing small pools at each intersection along the way.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recent experiments considering unsaturated flow in hydrophilic fracture networks have shown that capillary barriers formed at simple intersections between vertical and horizontal fractures can act to divert flow [ LaViolette et al , 2003], impose a temporal signal [ Glass et al , 2002; Wood et al , 2002], and/or block lateral spreading [ Glass et al , 2003]. While not fully understood, this complex behavior clearly results from a sudden change in the relative importance of capillary forces that rises from the difference in void geometry between an intersection and the contributing fractures.…”
Section: Introductionmentioning
confidence: 99%